A King’s Confectioner in the Orient - Işın, Priscilla Mary (Petits Propos Culinaires, 2002)
The author contributed a piece to PPC 61 on the nineteenth-century Turkish cookery book by Mahmud Nedim bin Tosun. Here, she introduces a very early German text describing Turkish confectionery.